To settle but not convert hukou among rural migrants in urban China: How does family-level eligibility for citizenship benefits matter?. (February 2022) - Zhou, Jing; Lin, Liyue; Tang, Shuangshuang; Zhang, Shuhai
Abstract: Since 2010, although Chinese governments have continued to relax hukou barriers and reduce the gap between rural and urban hukou, migrants are less enthusiastic than expected in taking the opportunity to convert to urban-hukou . However, understandings of such reversed attitudes have been insufficient, especially from an international perspective. This study thus brings theories of naturalisation and citizenship to examining hukou conversion. Using the China Migrants Dynamic Survey of 2017 (the only year that also investigated migrant families with local-hukou spouses), the study applies cross-classified multi-level logistic regressions to estimate how eligibility for exclusive benefits of urban citizenship at the family level affects rural-to-urban migrants' decisions on hukou conversion. Unlike previous research, this study examines explicitly rural-to-urban migrants who planned to settle in destination cities, which helps to extend understanding of the gap between the de facto settlement and the institutional settlement ( hukou conversion) among Chinese migrants. Moreover, the study fills the knowledge gap regarding the impact of family-level citizenship dynamics on hukou conversion decisions. Unlike in the international context where naturalised citizens and homeownership at the family-level promote naturalisation of other family members, we find that the family holding of local urban-hukou and ownership of formal housing suppress hukou conversion of migrant spouses, especially in less attractive cities and for migrants who feel either insecure in the job market or economically independent. The study argues that homeownership and having a local urban-hukou family member, both of which promote family-level access to local exclusive urban citizenship benefits, have a 'protection effect' which enables rural-to-urban migrant families to maximise their opportunities in rural hometowns and host cities without sacrificing rural citizen rights in exchange for urban-hukou . We predict an increasing emergence of such a family context and discuss the motivations of the Chinese state in these current policies concerning hukou conversion.